1987
DOI: 10.1159/000167444
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of the Nephrotic Syndrome in Sickle Glomerulopathy

Abstract: Of 240 adults with sickle cell anemia seen over 11 years, 12 had the nephrotic syndrome. In 9 (75%) the glomerular lesion, sickle glomerulopathy, consisted of mesangial expansion and basement membrane duplication. Six patients had type IV renal tubular acidosis. Four of the 9 Patients died within 24 months (17 ± 5; mean ± SD), while 5 survived 36 months or longer (80 ± 49); no significant differences were seen between the former and the latter in age, admission serum creatinine and C3 levels, urinary protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 11 publications
2
50
0
1
Order By: Relevance
“…However, in the present study proteinuria was not found. The rate of microalbuminuria was similar to the reports of Becton et al (9), but less than reports of Imuetiyan et al, Lenensburger et al, and . It is expected that micro-albuminuria is increased by aging and decreasing GFR (10,18).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, in the present study proteinuria was not found. The rate of microalbuminuria was similar to the reports of Becton et al (9), but less than reports of Imuetiyan et al, Lenensburger et al, and . It is expected that micro-albuminuria is increased by aging and decreasing GFR (10,18).…”
Section: Discussionsupporting
confidence: 86%
“…The development of chronic azotemia correlates strongly with poor prognosis and early mortality as compared to the general population of sickle cell anemia (9). GFR < 60 was present in 5.2% of our patients while end stage renal disease was not present.…”
Section: Discussionmentioning
confidence: 53%
“…Sickle cell-specific criteria included homozygous SCD, compound heterozygous hemoglobin S and C disease or hemoglobin S and b 0 -thalassemia disease, stroke, sickle cell-related renal insufficiency (defined by creatinine $1.5 times the upper limit of normal and kidney biopsy consistent with sickle cell nephropathy, or nephrotic syndrome or creatinine clearance ,50 mL/minute or requiring dialysis), [19][20][21] tricuspid regurgitant jet velocity $2.5 m/s, 22,23 sickle hepatopathy (defined as either ferritin $1000 mg/L or direct bilirubin .0.4 mg/dL and platelet count ,250 000/mL at baseline), 24 .1 hospitalization per year for vaso-occulsive crises or any acute chest syndrome while receiving a maximum tolerated dose of hydroxyurea for at least 6 months.…”
Section: Protocol Specificsmentioning
confidence: 99%
“…Full nephrotic syndrome is uncommon at approximately 4%, but when it does occur, it is associated with a very poor outcome. 17 A recognized trigger for nephrotic syndrome, which has been highlighted in patients with SCD, is a recent infection with human parvovirus B19. Early renal biopsy may demonstrate the collapsing variant of focal segmental glomerulosclerosis, the classical lesion associated with virus-induced glomerulopathy.…”
Section: Proteinuriamentioning
confidence: 99%